Pesticide Residues Analysis of Arabica Coffee Bean from Community Coffee Plantation Manglayang Mountain, Bandung Regency - Rasiska, Siska; Maharani, Yani; Hutapea, Dedi Hutapea; Maxiselly, Yudithia; Wulandari, Ela Hasri (CROPSAVER, 2024)
Coffee is one of the export commodities that has produced gross domestic product up to 16.15% of the agricultural sector. However, pesticide residues in agricultural products remain a barrier in the context of exports and agricultural product safety. The study aims to analyze the pesticide residue content in coffee produced by farmers at the Manglayang Mountain Community Coffee Plantation (CCP) compared to the maximum residue limit. The method used in this research is explorative descriptive by collecting samples from the Giri Senang Forest Community, Legok Nyenang-Giri Mekar Village, Cilengkrang District, Bandung Regency, and analyzed with the method EN 15662:2018. A kilogram of coffee is washed and dried for two days, then separated from the skin of the coffee and the green bean. The green bean are then extracted by QuEChERS, by adding 1% acetic acid in acetonitril and the extract is cleansed using high SPE  dispersive. LC-ESI-MS/MS is operated in MRM mode, and validated according to the SANTE 12682/2019 requirements. The results of the research showed that the coffee from was not detected containing residues of pesticides from the organophosphate and carbamate groups. Thus, the coffee products from Manglayang Mountain CCP are considered safe to be consumed, and can be exported abroad.